An Acoustical Simulation for the Muffler of Reciprocating Compressors Using the FEM Method. (October 2015) - Chiu, Min-Chie; Chang, Ying-Chun; Xie, Ji-Lin
A reciprocating compressor is commonly used in industry. However, because it is extremely noisy and harmful to the ears, a noise control mechanism is necessary. Eight kinds of noise control strategies used with the reciprocating compressor are explored, and COMSOL, a numerical analysis software, is adopted for acoustical analysis in the paper. The primary purpose of this research is to assess the influence of seven noise control strategies for the suction/discharge muffler of a reciprocating compressor. Results have shown that the noise control strategies can efficiently improve the acoustical performance of the suction/discharge mufflers.